Beyond the Office: Navigating Ergonomic Mismatch and Psychosocial Challenges in Long-Term Remote Work - Serpian, Serpian; Asmar, Kurniati; Hirman, Hirman; Rahmatillah, Rahmatillah; Abdul-Rahaman, Osman (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2026)
This study examines the in-depth experiences of long-term remote workers as they navigate physical and psychosocial challenges within their domestic environments. By integrating a Macroergonomics perspective and Interpretative Phenomenological Analysis (IPA), it addresses the gap in reductionist literature that separates physical pain from mental stress. We frame home ergonomics as a complex ecosystem involving space negotiation and